2015
DOI: 10.1111/acps.12506
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term suicide risk in no, one or more mental disorders: the Lundby Study 1947–1997

Abstract: ObjectiveTo investigate long‐term suicide risk in individuals with no, one or more mental disorders.MethodIn the Lundby Study, involving a total population of 3563 subjects, mental health and suicide risk were monitored over 54–64 years.ResultsThe long‐term suicide risk in subjects with no, one, or more mental disorders was 0.3%, 3.4% and 6.2% respectively. For individuals with only depression, the risk was 6.0%, only alcohol use disorder 4.7%, and only psychosis 3.1%. However, when individuals had additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
37
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 41 publications
7
37
0
1
Order By: Relevance
“…The effect estimates remained almost unchanged across the different univariate and multivariate models, suggesting an elevated robustness. The studied location, a catchment area with universal health coverage, combines different city districts and rural areas, including a wide range of ages, nationalities, and socioeconomical contexts (Hortas & Onrubia, 2017). In addition to the mentioned coincidence with previous results from other places and health systems, the heterogeneity of patient profiles and social contexts included provides grounds for our results to be considered widely generalizable, especially to settings with universal medical coverage.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…The effect estimates remained almost unchanged across the different univariate and multivariate models, suggesting an elevated robustness. The studied location, a catchment area with universal health coverage, combines different city districts and rural areas, including a wide range of ages, nationalities, and socioeconomical contexts (Hortas & Onrubia, 2017). In addition to the mentioned coincidence with previous results from other places and health systems, the heterogeneity of patient profiles and social contexts included provides grounds for our results to be considered widely generalizable, especially to settings with universal medical coverage.…”
supporting
confidence: 65%
“…As an addition, our study offers updated information on several clinical and sociodemographical risk factors for suicide and suicide attempts. As previously published in studies from a variety of international locations, female gender, previously diagnosed psychiatric disorders, and drug or alcohol abuse carried higher risk (Beghi, Rosenbaum, Cerri, & Cornaggia, ; Christiansen & Jensen, ; Holmstrand et al., ). A recent cohort study, conducted in Barcelona, Spain, found an increased risk in younger groups (Parra‐Uribe et al., ), a finding that was absent in our study.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The answer options were: no impairment (0), mild impairment (1), moderate impairment (2), or severe impairment (3). Considering the threshold for defining impairment is subjective and personal, as a conservative approach we considered impairment if the individual reported the condition caused moderate or severe impairment, as already adopted by other authors 6 .…”
Section: Methodsmentioning
confidence: 99%
“…Poor mental health in youth is strongly related to other health and development problems (i.e. lower educational achievement, substance abuse, violence and poor reproductive and sexual health) 5 , as well as higher risk of suicide 6,7 . During mid-adolescence and emerging adulthood (15-29 years) suicide represents the second leading cause of death in the world, and the fourth in Brazil 8,9 , and about 75% of the suicide deaths in the world occur in low-and middle-income countries 4 .…”
Section: Introductionmentioning
confidence: 99%